The Effect of Enterprise Resource Planning (ERP) System Implementation, User Training, and Management Support on User Satisfaction in Manufacturing Companies - Sudarmo, Sudarmo; Vandika, Arnes Yuli; Fahrijal, Rival (Westscience Press, 2024)
This study examines the impact of Enterprise Resource Planning (ERP) system implementation, User Training, and Management Support on User Satisfaction within manufacturing companies. Using a quantitative approach, data were collected from 160 respondents and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that all three factors—ERP system implementation, User Training, and Management Support—have a positive and significant effect on User Satisfaction. Among these, User Training emerged as the most influential factor, followed by Management Support and ERP system implementation. These findings underscore the critical role of human-centric factors in ensuring successful ERP adoption and highlight the importance of comprehensive training and strong management involvement. The study offers practical insights for organizations aiming to enhance user satisfaction with ERP systems, emphasizing the need for a holistic approach that integrates technical and human factors.